Сборник тестов и заданий по теории бухгалтерского учета - Богатая И. Н. Ирина Николаевна; Чешев А. С. Анатолий Степанович; Бородин И. А. Иван Афанасьевич; Фесенко И. П. Иван Павлович; Рагрин В. Н. Виктор Николаевич (Ростов-на-Дону, Экспертное бюро, 2004)
Исключено из фонда НТБ ТПУ